2010
DOI: 10.1021/nn901926r
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Carbon Nanocoils from K and Ag Cooperative Bicatalyst Assisted Thermal Decomposition of Acetylene

Abstract: Growth of amorphous carbon nanocoil (CNC) from acetylene on Si substrates was achieved by using nanosized Ag and K as the catalysts. The deposition of CNC was carried out inside a hot-wall reactor at 723 K using H2 as the carrier gas. Based on the observed results, we propose a cooperative bimetal catalyst enhanced vapor-liquid-solid (VLS) growth mechanism to rationalize the CNC growth. In the reaction, the liquid phase metallic K dehydrogenated acetylene into the solid-state carbon, while the Ag nanoparticle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…These nanostructures have generally been referred to as carbon nanocoils (CNCs), and have been investigated for implementation in numerous applications, for instance in structural cushions (nanosprings) [3], field emission displays [4,5], and as magnetic components [6]. To fulfil the rational use of helical carbons, various approaches towards synthesis have been attempted to gain control over the structures and hence the properties of the products.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These nanostructures have generally been referred to as carbon nanocoils (CNCs), and have been investigated for implementation in numerous applications, for instance in structural cushions (nanosprings) [3], field emission displays [4,5], and as magnetic components [6]. To fulfil the rational use of helical carbons, various approaches towards synthesis have been attempted to gain control over the structures and hence the properties of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical vapor deposition (CVD) is the most commonly used synthesis technique for CNCs and the catalyst material employed within the CVD reactions plays a crucial role [4,7,8]. It was shown that the size, shape, and yield of the grown nanostructures are governed by the chemical and geometrical features of the catalyst [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the typical catalyst materials such as transition metals Fe, Co and Ni, several novel metal catalysts have also been developed such as Cu, Ag and K [30,31]. However, the catalytic properties of the magnetic metal oxides, a less costly and more accessible catalyst, have not received as much attention and the associated growth mechanism of HCNTs based on such catalysts remains elusive to this date.…”
Section: Introductionmentioning
confidence: 99%